A 5‐hour follow‐up of the impact on ageing facial signs of some foundations in Japanese women through automatically analysed selfie pictures. (12th July 2022) - Flament, Frederic; Velleman, Damien; Yamashita, Eri; Nicolas, Alexandre; Yokoyama, Emilie; Chibout, Salim; Jiang, Ruowei; Houghton, Jeff; Kroely, Camille; Cassier, Matthieu
Abstract: Objective: To explore the possibility of an automatic grading algorithm to detect and quantify, from selfie pictures, the subtle changes of facial signs brought by the application of a foundation. Material and Methods: A total of 270 Japanese differently aged women (30–54y) living in four different Japanese cities took selfies before, immediately and 5 h after having applied their own foundation, with their own routine. Results: The analysis of 810 selfie pictures revealed (3 times × 270 women) that, prior to applications, all women presented a low grade of facial ageing. In most cases, the severities of less marked facial signs were detected and quantified, found affected by routine at different extents in all age‐classes, but more intensely in the older age‐class (45–54y) despite their more pronounced signs in bare skin status. In contrast, periorbital wrinkles were detected as more severe in all age‐classes at both timing, that is, immediately and 5 h post‐application as well as Nasolabial folds 5 h post‐application. The amplitude of these positive or negative changes, although found of low amplitude, as decimals of the initial grades, was significantly detected. Conclusion: This automatic system appears apt at grading subtle changes in facial ageing signs brought by a foundation and could be a valuable help to the consumers of make‐up products, in refining their individual procedure to obtain a more personalized desired facial appearance. Résumé: Objectif: Explorer la possibilité pour un algorithme de scorage automatique des signes faciaux de détecter et quantifier sur la base de photographies 'selfies', les changements subtils apportés par l'application et la tenue de fonds de teint. Matériel et Méthodes: 270 femmes japonaises âgées de 30 à 54 ans et vivant dans 4 villes différentes ont pris des selfies sur la base de leur smartphone avant, immédiatement et 5 heures après avoir appliqué leurs routines cosmétiques incluant leur propre fond de teint. Résultats: L'analyse des 810 selfies (3 temps×270 femmes) a révélé que, avant application, la plupart des femmes présentent des grades faibles de vieillissement facial. Dans la plupart des cas, les sévérités des signes les moins marqués, détectés et quantifiés, a été trouvée affectée à différents niveaux dans toutes les classes d'âge, mais plus intensément pour les volontaires les plus âgées (45 à 54 ans) en dépit de leurs valeurs plus élevées sur peau nue. A contrario, les rides péri‐orbitales ont été mesurées comme plus sévères dans toutes les classes d'âge à tous les temps, c'est‐à‐dire immédiatement et 5 heures apprès application du fond de teint tandis que le sillon nasogénien a été observé comme plus sévère 5 heures après application. L'amplitude de ces changements positifs ou négatifs, bien que faible avec des valeurs décimales des grades initiaux, a été significativement détectée. Conclusions: Le système de scorage automatique apparaît capable d'évaluer des changements subtils dans les signes de vieillissement faciaux apportés par l'application de fonds de teint et se révèle une aide intéressante aux consommateurs de produits de maquillage pour affiner leurs routines individuelles afin d'obtenir des résultats plus personnalisés sur l'apparence désirée.